PERAN DAN PERKEMBANGAN GREEN SUKUK PADA PEMBANGUNAN INFRASTRUKTUR DI INDONESIA - Jihan Nabila (AKRUAL : Jurnal Akuntansi dan Keuangan, 2024)
Sustainable development aims to open up opportunities for the issuance of Sukuk (Sharia Securities) as an alternative sustainable financing for infrastructure development in Indonesia, along with public awareness of the concept of sustainable and environmentally friendly development, a new investor market has been launched. Green Sukuk emerged as an investment for various government projects that are included in the 9 eligible green sectors. This research resulted in the conclusion that the green sukuk that have been issued in Indonesia have contributed to sustainable development goals in accordance with goal 7, goal 8, goal 9, goal 11 and goal 13.